FAKTOR – FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DAN RETURN SAHAM - Ryan Ryangga; Yuli Chomsatu S; Suhendro Suhendro (STIE Muhammadiyah Jakarta, 2020)
This study aims to examine the effect of profitability on firm value and stock returns, liquidity on firm value and stock returns, and firm size on firm value and stock returns. This research uses data from 4 automotive companies. and components listed on the Indonesia Stock Exchange during the period 2009 to 2018 using multiple linear regression analysis. The sampling technique was using purposive sampling method. The results showed that profitability using ROA and firm size has an effect on firm value. Profitability with ROA and ROE proxies has an effect on stock returns. ROE and liquidity have no effect on firm value. Liquidity and firm size have no effect on stock returns.